Crime, compulsory schooling laws and education. (October 2016) - Bell, Brian; Costa, Rui; Machin, Stephen
Highlights: We reconsider causal evidence on crime and education driven by changes in compulsory school laws. There is a strong and consistent negative effect on crime from stricter compulsory schooling laws. There is a weaker link between such laws and educational attainment when the more recent experience is considered. Credible causal estimates of the education–crime relationship prove difficult to identify for some groups in the more recent period. Abstract: Do compulsory schooling laws reduce crime? Previous evidence for the US from the 1960s and 1970s suggests they do, primarily working through their effect on educational attainment to generate a causal impact on crime. In this paper, we consider whether more recent experience replicates this. There are two key findings. First, there is a strong and consistent negative effect on crime from stricter compulsory schooling laws. Second, there is a weaker and sometimes non-existent link between such laws and educational attainment. As a result, credible causal estimates of the education–crime relationship cannot in general be identified for the more recent period, though they can for some groups with lower education levels (in particular, for blacks).